Modeling and validation of a new reconfigurable patch antenna through equivalent lumped circuit‐based design for minimum tuning effort. Issue 6 (22nd February 2020) - Koc Polat, Hilal; Geyikoglu, Miraç D.; Cavusoglu, Bulent
Abstract: This study presents a modeling of a new reconfigurable patch antenna with equivalent lumped circuit. Instead of intuitive approaches, including structural changes used in the literature, the proposed reconfigurable antenna design is based on minimum tuning effort using only capacitance adjustments. The proposed design resolves impedance mismatch problem, which occurs due to the nature of using several frequencies by only capacitance adjustments rather than physical structure adjustments. Reconfigurable patch antenna for 2.45 GHz (Wi‐Fi), 3.6 GHz (Wi‐max and 5G), 5.4 GHz (WLAN and 5G) was considered for novel design strategy. A complete equivalent circuit model is configured and validated through AWR software. Full wave analysis of the proposed antenna is performed using CST software. A prototype of the proposed antenna is also fabricated on a FR4 substrate with the dimensions of 48.19 x 38.36 x 1.53 mm 3 and measured to validate the full wave analysis and circuit theory solution results. It is shown that the equivalent circuit model, full wave analysis, and measurement results are in good agreement.